The effect of phospholipase Dα3 on Arabidopsis response to hyperosmotic stress and glucose - Hong, Yueyun (Landes Bioscience, 2008)
Membranes are the primary sites of perception for extracellular stimuli and are rich sources for signaling messengers. Phospholipase D (PLD) hydrolyzes membrane lipids to produce the messenger phosphatidic acid (PA), and the activation of PLD occurs under different hyperosmotic stresses, including dehydration and salt stress. We have recently found that PLDα3 that plays a positive role in hyperosmotic stress. PLDα3 hydrolyzes multiple substrates with distinguishable preferences. The involvement of PLDα3 in hyperosmotic stress is through a different mechanism from that PLDα1, which mediates the effect of abscisic acid on stomatal movements. PLDα3 enhances root growth and accelerates flowering time under hyperosmotic stress. Alterations of PLDα3 affect the level of PA, transcripts of TOR and AGC2.1, ABA-responsive genes, and phosphorylated S6K protein under hyperosmotic stress. Our further observation shows that PLDα3 is also involved in glucose response. PLDα3-KO seeds and seedlings are less sensitive to glucose whereas PLDα3-overepressed seeds are more sensitive than wild type. These results point to a possibility that PLDα3-mediated lipid signaling may play a role in integrating nutrient sensing, protein kinase activation, and hormones responses to regulate growth and development under hyperosmotic stress.